A new species of Meharia Chrétien, 1915 (Lepidoptera, Cossidae) from the United Arab Emirates, with a world catalogue of the genus - Yakovlev, Roman V. (Zootaxa, 2014)
Meharia breithaupti sp. nov. is described from the United Arab Emirates.